2009
DOI: 10.1177/1753425909105548
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin tolerance does not limit mild ischemia-reperfusion injury in humans in vivo

Abstract: Animal studies have shown that previous exposure to lipopolysaccharide (LPS) can limit ischemia-reperfusion injury. We tested whether pretreatment with LPS also protects against ischemia-reperfusion injury in humans in vivo. Fourteen volunteers received bolus injections of incremental dosages of LPS on 5 consecutive days (LPS group). Before the first and 1 day after the last LPS administration, the forearm circulation of the non-dominant arm was occluded for 10 min, with concomitant intermittent handgripping t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Although very low circulating cytokine levels were found, a small, but significant attenuation of TNF-␣, IL-6, and IL-1RA plasma levels was observed upon the second LPS administration (18). Earlier work from our group has shown that after LPS administration for 5 consecutive days in healthy volunteers, the cytokine response is virtually nullified at day 5 (11,19), and similar results were observed in LPStreated cancer patients (20).…”
Section: Discussionsupporting
confidence: 86%
“…Although very low circulating cytokine levels were found, a small, but significant attenuation of TNF-␣, IL-6, and IL-1RA plasma levels was observed upon the second LPS administration (18). Earlier work from our group has shown that after LPS administration for 5 consecutive days in healthy volunteers, the cytokine response is virtually nullified at day 5 (11,19), and similar results were observed in LPStreated cancer patients (20).…”
Section: Discussionsupporting
confidence: 86%
“…Published i n vivo studies show a general decrease in inflammatory cytokine production from macrophages after repeated LPS dosing, a phenomenon known as LPS or endotoxin tolerance [39, 40]. This effect is considered a natural cellular response to prevent uncontrolled inflammation [41–43], and is readily apparent in cultured primary-derived macrophages in this and other studies [44].…”
Section: Discussionmentioning
confidence: 73%
“…102 In the same model, endothelial dysfunction gradually declines as endotoxin tolerance emerges, 136 whereas LPS tolerance does not seem to protect against ischemia-reperfusion injury. 137 The repeated-exposure model has also been used for the study of sepsis-induced immunoparalysis, where IFN-γ treatment has partially reversed immune suppression and furthered pharmacologic interest for immunostimulation in sepsis. 138 Though these findings provide key initial insights into the elements of endotoxin tolerance, much research is still needed to elucidate the role of repeated LPS exposure on cardiometabolic physiology.…”
Section: Limitations and Challenges Of The Modelmentioning
confidence: 99%